2021
DOI: 10.1097/md.0000000000026296
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of cold snare polypectomy for small colorectal polyps

Abstract: Trial design: Elimination of small colorectal polyps with cold snare polypectomy (CSP) is reported to be as safe as hot snare polypectomy (HSP). The effectiveness of CSP has not been clearly defined, and the incidence of long-term recurrence has not been determined. We conducted a randomized control study and one-year follow-up study to assess their safety and efficacy. Methods: Patients with small colorectal polyps were randomized to receive CSP or HSP. Polypectomy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…And after excluding articles using R0 resection rate, sensitivity analysis showed similar outcome to our primary analysis. Meanwhile, as the most accurate evaluation method, recent RCTs also found higher rates of polyp recurrence in the CSP group in follow-up colonoscopy, although with no statistically significant difference (28,33,35). More high-quality evidence on findings at surveillance colonoscopy is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…And after excluding articles using R0 resection rate, sensitivity analysis showed similar outcome to our primary analysis. Meanwhile, as the most accurate evaluation method, recent RCTs also found higher rates of polyp recurrence in the CSP group in follow-up colonoscopy, although with no statistically significant difference (28,33,35). More high-quality evidence on findings at surveillance colonoscopy is needed.…”
Section: Discussionmentioning
confidence: 99%
“…A flow 10.3389/fmed.2023.1154411 chart of the trial selection process is shown in Figure 1. Fourteen articles compared HSP with CSP, (15,16,21,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) three articles compared HSP to EMR, (31, 36, 37) three articles compared CSP to CS-EMR, (31,38,39) two articles compared CSP to EMR, (31, 40) two articles compared CSP to UCSP, (41,42) one article compared CS-EMR to EMR, (43) one article compared UEMR to EMR, (44) and one article compared APC to HSP and CSP (33). All studies were published after 2010, and nine studies were multicenter studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic treatments, including endoscopic submucosal dissection, have been accepted as reliable and less invasive treatment even for large intestinal lesions 1 2 3 . Among them, cold snare polypectomy without high-frequency generators recently has been accepted as an easy and simple way to resect precancerous lesions < 10 mm in diameter, especially in periodic colonoscopy after a patient’s colon is disease-free 4 5 6 7 8 . It enables resection of polyps with less damage to residual tissue surrounding the resected lesion.…”
Section: Introductionmentioning
confidence: 99%